PENYATUATAPAN PERADILAN AGAMA (SUATU PERSPEKTIF DINAMIKA SEJARAH) - Abd Khalik Latuconsina (IAIN Ambon, 2017)
Religious Courts, as well as the judiciary, the New Order era was on two roofs, or power (judicial and executive). But after adannya Act No. 5 of 2004, concerning Amendment to Law No. 14 Year 1985 regarding the Supreme Court, the Religious Courts have under one roof, namely the Supreme Court. It was in accordance with Law No. 3 of 2006 on amendments to the Law No. 7 of 1989 on Religious Courts. Through this latest legislation, the Religious Courts the authority to examine the dispute in the field of Islamic economics. Keywords: putting, the judiciary religious, historical dynamics